2016
DOI: 10.4178/epih.e2016048
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status of people isolated due to Middle East Respiratory Syndrome

Abstract: OBJECTIVESIsolation due to the management of infectious diseases is thought to affect mental health, but the effects are still unknown. We examined the prevalence of anxiety symptoms and anger in persons isolated during the Middle East Respiratory Syndrome (MERS) epidemic both at isolation period and at four to six months after release from isolation. We also determined risk factors associated with these symptoms at four to six months.METHODSOf 14,992 individuals isolated for 2-week due to having contact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
902
9
73

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 997 publications
(1,088 citation statements)
references
References 13 publications
55
902
9
73
Order By: Relevance
“…However, another study 16 release from quarantine. 17 Healthcare workers 25 who had been quarantined had more severe symptoms of post traumatic stress than members of the general public who had been quarantined, scoring significantly higher on all dimensions. Healthcare workers also felt greater stigmatisation than the general public, exhibited more avoidance behaviours after quarantine, reported greater lost income, and were consistently more affected psychologically: they reported substantially more anger, annoyance, fear, frustration, guilt, helplessness, isolation, loneliness, nervousness, sadness, worry, and were less happy.…”
Section: Prequarantine Predictors Of Psychological Impactmentioning
confidence: 95%
See 4 more Smart Citations
“…However, another study 16 release from quarantine. 17 Healthcare workers 25 who had been quarantined had more severe symptoms of post traumatic stress than members of the general public who had been quarantined, scoring significantly higher on all dimensions. Healthcare workers also felt greater stigmatisation than the general public, exhibited more avoidance behaviours after quarantine, reported greater lost income, and were consistently more affected psychologically: they reported substantially more anger, annoyance, fear, frustration, guilt, helplessness, isolation, loneliness, nervousness, sadness, worry, and were less happy.…”
Section: Prequarantine Predictors Of Psychological Impactmentioning
confidence: 95%
“…Participants in eight studies reported fears about their own health or fears of infecting others 9,13,14,16,17,21,25,26 and were more likely to fear infecting family members than those not quarantined. 9 They also became particularly worried if they experienced any physical symptoms potentially related to the infection 14 and fear that the symptoms could reflect having the infection continued to be related to psychological outcomes several months later.…”
Section: Fears Of Infectionmentioning
confidence: 99%
See 3 more Smart Citations